Mammalian skull heterochrony reveals modular evolution and a link between cranial development and brain size - Koyabu, Daisuke (2014)
The multiple skeletal components of the skull originate asynchronously and their developmental schedule varies across amniotes. Here we present the embryonic ossification sequence of 134 species, covering all major groups of mammals and their close relatives. This comprehensive data set allows reconstruction of the heterochronic and modular evolution of the skull and the condition of the last common ancestor of mammals. We show that the mode of ossification (dermal or endochondral) unites bones into integrated evolutionary modules of heterochronic changes and imposes evolutionary constraints on cranial heterochrony. However, some skull-roof bones, such as the supraoccipital, exhibit evolutionary degrees of freedom in these constraints. Ossification timing of the neurocranium was considerably accelerated during the origin of mammals. Furthermore, association between developmental timing of the supraoccipital and brain size was identified among amniotes. We argue that cranial heterochrony in mammals has occurred in concert with encephalization but within a conserved modular organization.